A new species of Reissantia (Celastraceae) from coastal Karnataka, India - Page, Navendu V.; Srivastav, Mansa; Rao, Ramachandra G. (Phytotaxa, 2017)
Reissantia N. Hallé (1958: 466) is a small but widespread genus distributed in the Old World tropics of Africa and Indo-Malaya (Ramamurthy and Naithani, 2000). Members of Reissantia are climbing, scandent or erect shrubs with decussate leaves. They are characterised by small flowers borne in dichotomous cymes or panicles with accessory branches, small calyx and corolla with imbricate aestivation, inconspicuous disc that is mostly fused with the ovary, 3 stamens inserted at the base of the carpel, 3-locular ovary and 3-fascicled capsular fruit with seeds that have a basal membranous wing.